Molecular and microbiological characterisation of an acinetobacter sp., isolated from petroleum-contaminated soil in Sentul, Kuala Lumpur, Malaysia - Merican, A.F.; Ezaki, T.; Dass, A.; Hussin, H.; Awaluddin, R.; Kamarudin, M.R. (Malaysian Society for Molecular Biology and Biotechnology, 2002)
A bacteria isolated from a petroleum-contaminated soil was characterised using molecular and microbiological methods. Strain PCS was able to utilized medium and long chain n-alkanes. Following phylogenetic analysis based on partial 16S rRNA gene sequence, this bacteria was placed in the genus Acinetobacter. Acinetobacter baumannii was the most closely related species in the phylogenetic tree. Based on the pylogenetic analysis, this strain may possibly be a new Acinetobacter sp.